Efektivitas Limbah Puntung Rokok sebagai Inhibitor Korosi dalam Medium Asam Klorida pada Baja A36 dengan Metode Microwave Assisted Extraction: Effectiveness of Cigarette Butts Waste as Corrosion Inhibitor in Hydrochloric Acid Medium on A36 Steel by Microwave Assisted Extraction Method - Alatif, Ikhsan Akmal; Permatasari, Rahma Puspa; -, Maya Futri Nur Rachmat; Wulandari, Dwi Arsya; Sonia, Gina; Aura, Azma Addina; Trirahayu, Dhyna Analyes; Hadiningrum, Kunlestiowati (KOVALEN: Jurnal Riset Kimia, 2024)
Cigarette butts are one of the wastes found in many places, and their presence can damage the environment. One way to reduce the amount of cigarette butts waste is to process them into corrosion inhibitors. This study aims to extract tobacco from cigarette butts using 96% ethanol solvent by varying the extraction time for 5, 10, 15, and 20 minutes, and microwave power of 150 watts and 300 watts, and calculating the efficiency of corrosion inhibitors in acidic environments. The extraction method used was Microwave Assisted Extraction (MAE). From the extraction process, it is known that the optimum extraction power of 150 watts in 15 minutes produces the highest yield of 64.52%. Based on phytochemical and GC-MS tests, it is known that cigarette butt extract contains antioxidant compounds in the form of alkaloids, pyranones, and terpenoids as corrosion inhibitor compounds. Based on corrosion testing, it is proven that the addition of cigarette butt waste extract corrosion inhibitors can suppress or reduce the corrosion rate that occurs on metals with the most excellent efficiency of 82.26% with an extract concentration of 2000 ppm. And the SEM-EDX test results concluded that the corrosion inhibitor from cigarette butts waste extract can withstand the formation of rust on the metal.